Community health workers at the dawn of a new era: 7. Recent advances in supervision - Carey Westgate; David Musoke; Lauren Crigler; Henry B. Perry (BMC, 2021)
Abstract Background Supervision is essential for optimizing performance and motivation of community health workers (CHWs). This paper, the seventh in our series, "Community health workers at the dawn of a new era", supplements the existing evidence on CHW supervision in low- and middle-income countries by reviewing what supervision approaches are employed in specific contexts, identifying potential facilitators of CHW supervision including mobile health (mHealth) interventions, and noting challenges of supervision including the relationship between supervision and other CHW programme elements. Methods For this exploratory research study on CHW supervision, we reviewed the supervisory interventions described in a compendium of 29 case studies of large-scale CHW programmes, performed an electronic search of multiple databases to identify articles related to CHW supervision published between 15 June 2017 and 1 December 2020, and from those articles followed additional references that appeared to be relevant for our results. Results We reviewed 55 case studies, academic articles, and grey literature resources as part of this exploratory research. A variety of supervision approaches have been adapted over time, which we grouped into five categories: external supervision, community supervision, group supervision, peer supervision, and dedicated supervision. These approaches are frequently used in combination. Digital (mHealth) technologies are being explored as potential facilitators of CHW supervision in both small- and large-scale programmes; however, evidence of their effectiveness remains limited to date. Inadequate support for supervisors is a major challenge, particularly given the numerous and varied roles they are expected to fulfil, spanning administrative, clinical, and supportive activities. Supervisors can help CHWs acquire other critical elements needed from the health system for them to perform more effectively: incentives to foster motivation, clarity of roles and tasks, adequate tools and supplies, appropriate knowledge and skills, and a safe work environment. Conclusion In the absence of a universal "best approach" for CHW supervision, our recommendation is that countries and programmes prioritize homegrown evolution over time to suit the local context. In some cases, this may involve scaling up novel approaches that have proven effective at small scale or testing approaches that have worked in other countries.